Prevalence and correlates of suicide attempts in Chinese individuals with borderline personality disorder - Yang, Fan; Tong, Jun; Zhang, Shu-Fang; Zhang, Juan; Zhong, Bao-Liang (Frontiers in Psychiatry, 2022)
Background: To date, few empirical studies have examined the clinical characteristics of suicide attempts (SA) in individuals with borderline personality disorder (BPD) in China. Aims: To examine the prevalence and factors associated with SA in Chinese individuals with BPD. Methods: In this cross-sectional study, 84 patients with BPD were recruited from a large public psychiatric hospital in Wuhan, China, between 2013 and 2015. Trained experienced psychiatrists interviewed participants to collect clinical data, including demographics, axis I and axis II diagnoses of mental disorders according to the DSM-IV-TR, number of hospitalizations, and history of SA. An interview outline was used to identify the existence of lifetime SA. In addition, the Beck Depression Inventory-II, Buss & Perry Aggression Questionnaire, Child Trauma Questionnaire-Short Form, and Beck Hopelessness Scale were administered to assess respondents’ depressive symptoms, aggression, childhood traumatic experiences, and hopelessness. Results: 52 (61.9%) patients reported attempting suicide during their lifetime. Univariate logistic regression analysis screened 7 factors associated with SA in individuals with BPD into Multiple logistic regression analysis: female sex, unemployment, major depressive disorder (MDD), hostility, self-aggression, depressive symptoms, and emotional neglect. Multiple logistic regression analysis identified 3 significant and independent correlates of SA: MDD (odds ratio [OR]=26.773, 95% confidence interval [CI]=3.914–183.132, P=0.001), hostility (OR=1.073, CI=1.019–1.130, P=0.007), and self-aggression (OR=1.056, CI=0.998–1.119, P = 0.060). Conclusions: Chinese individuals with BPD have a high risk of suicide. Correlates of SA in this population differ to some extent from those in Western populations as reported in the literature. Paying attention to MDD and some types of aggression in Chinese individuals with BPD may help identify their risk of suicide. Future large-sample cohort study may improve the limitations of this study and further confirm the point of view above.